2021
DOI: 10.4168/aair.2021.13.5.762
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab Therapy Improves Stratum Corneum Hydration and Skin Dysbiosis in Patients With Atopic Dermatitis

Abstract: Purpose We aimed to investigate the effects of dupilumab on 1) the permeability and antimicrobial barrier, 2) the composition of the skin microbiome, and 3) the correlation between changes in skin barrier properties and microbiota in atopic dermatitis (AD) patients. Methods Ten patients with severe AD were treated with dupilumab for 12 weeks. Disease severity was assessed using the Eczema Area and Severity Index (EASI). Skin barrier function was evaluated by measuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Some other studies have also evaluated the impact of dupilumab on skin barrier function [ 46 , 47 , 48 , 49 , 50 ]. They showed that dupilumab reduced TEWL on non-involved and involved skin [ 46 , 47 , 48 , 49 , 50 ]. The impact of dupilumab in SCH differs between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have also evaluated the impact of dupilumab on skin barrier function [ 46 , 47 , 48 , 49 , 50 ]. They showed that dupilumab reduced TEWL on non-involved and involved skin [ 46 , 47 , 48 , 49 , 50 ]. The impact of dupilumab in SCH differs between studies.…”
Section: Discussionmentioning
confidence: 99%
“… 168 In a small study, 12 weeks of Dupilumab treatment significantly increased SC hydration (L and NL) and this barrier improvement correlated with EASI improvement. 169 These studies suggest that Th2 inflammation is responsible for a number of epidermal abnormalities observed in AD subjects. Future studies will need to investigate how changes seen at early time points may predict later improvement in barrier and disease severity.…”
Section: How Barrier Defects Lead To Admentioning
confidence: 96%
“…Binding of cytokines to type I and type II receptors activates the JAK1/STAT6 pathway in hematopoietic and non-hematopoietic cells ( 37 ). These type 2 cytokines also cause skin barrier damage and increase the colonization of S. aureus ( 38 ). Barrier defects also induce keratinocyte production of IL-23, which leads to the activation of IL-23R expressing DCs triggering the Th22 immune response.…”
Section: Atopic Dermatitismentioning
confidence: 99%